ISOLASI BIOSURFAKTAN DARI LIMBAH CAIR KELAPA SAWIT : PENDEKATAN METODE EMULSIFICATION ACTIVITY, OIL DISPLACEMENT AREA DAN DROP COLLAPSE - Norholis Majid; Akhmad Riva'i (PROSIDING SEMINAR KIMIA, 2013)
Emulsification activity, drop collapsing as well as oil displacement test were used to determine biosurfactant producing bacteria consortium activity from palm oil mill effluent (POME). Samples were collected from waste water treatment in PTPN XIII Palm Oil Mill Factory, Paser Regency, EastKalimantan, Indonesia. Total of six samples were screened in order to find out which consortium was producing biosurfactant. All of the samples were showing activity in the drop collapsing method, but only sample #5 and #6 were showing Emulsification activity of 50 and 14%, respectively. Moreover,sample #5 and #6 were showing oil displacement activity which have 0.37 cm and 0.26 cm in diameter, respectively.